Optimal Decomposition of Service Level Objectives into Policy Assertions - Yousef Rastegari; Fereidoon Shams (The Scientific World Journal)
WS-agreement specifies quality objectives that each partner is obligated to provide. To meet quality objectives, the corresponding partner should apply appropriate policy assertions to its web services and adjust their parameters accordingly. Transformation of WS-CDL to WSBPEL is addressed in some related works, but neither of them considers quality aspects of transformation nor run-time adaptation. Here, in conformance with web services standards, we propose an optimal decomposition method to make a set of WS-policy assertions. Assertions can be applied to WSBPEL elements and affect their run-time behaviors. The decomposition method achieves the best outcome for a performance indicator. It also guarantees the lowest adaptation overhead by reducing the number of service reselections. We considered securities settlement case study to prototype and evaluate the decomposition method. The results show an acceptable threshold between customer satisfaction—the targeted performance indicator in our case study—and adaptation overhead.